Legume Productivity and Soil Nitrogen Dynamics in Lowland Rice-Based Cropping Systems - Ladha, J.K.; Kundu, D.K.; Angelo-Van Coppenolle, M.G.; Carangal, V.R.; Peoples, M.B.; Dart, P.J. (Wiley, 1996)
Rice (Oryza sativa L.) in wet season (WS) preceded by a dry season (DS) fallow, commonly practiced in rainfed lowlands, causes large losses of N through NO3 leaching and denitrification. The green‐manure legumes as NO3 catch crops is economically unattractive to farmers. In a 2‐yr study, we (i) assessed productivity of one grain and four forage legumes (pigeonpea [Cajanus cajan (L.) Millsp.], crotalaria (Crotalaria juncea L.), clitoria (Clitoria ternatea L.), desmanthus [Desmanthus virgatus (L.) Willd.], and siratro [Macroptilium atropurpureum (Mocino and Sessé ex DC.) Urban]) grown in the DS, (ii) examined NO3‐N and NH4‐N dynamics in soil (a Typic Tropaquept), and (iii) evaluated legume residues as a N source for succeeding rice. Nitrate‐N was dominant in the 30‐cm topsoil and was higher under legumes compared with weedy fallow. The legumes produced 4.9 to 9.1 t aboveground biomass ha‐1, accumulated 132 to 306 kg N ha‐1 of which 67 to 81% was derived from N2 fixation. After harvests, 2.9 to 5.2 t ha‐1 of residues containing 81 to 162 kg N ha‐1 were returned to soil. By 3 to 4 wk after flooding, legume‐treated plots had as much as 33 to 40 kg mineral N ha‐1 in topsoil compared with 10 to 13 kg N ha‐1 in weedy fallowed plots. Residues significantly increased rice yield and N uptake. Rice recovered 15 to 31% of the residue N. Failow plots required 25 to 50 kg fertilizer N ha‐1 to produce comparable plant growth responses to that obtained after the legumes. Belowground residues of the legumes apparently contributed 13 to 37 kg N ha‐1 to rice. Such DS legumes that improve farm productivity as well as increase soil fertility might ensure sustainability of production in rainfed lowlands.